Rhodium-carbonyl complexes with a quinolyl functionalized Cp-ligand: synthesis and photochemical activation - Enders, Markus; Kohl, Gerald; Pritzkow, Hans (Journal of organometallic chemistry, 2004)
Dicarbonyl[η5-2,3,4,5-tetramethyl-1-(8-quinolyl)cyclopentadienyl]rhodium(I) (1) was prepared by the reaction of [Rh(CO)2Cl]2 with 2,3,4,5-tetramethyl-1-(8-quinolyl)cyclopentadienyl-potassium. Irradiation of 1 in chloroform or dichloromethane as solvent leads to the formation of dichloro[η5-2,3,4,5-tetramethyl-1-(8-quinolyl)cyclopentadienyl]rhodium(III) (2). When Rh6(CO)16 is present, the cluster adds to the 8-quinolyl-cp-rhodium fragment and the compound [η5-2,3,4,5-tetramethyl-1-(8-quinolyl)cyclopentadienyl]rhodium-di-μ-carbonyl-hexarhodiumtetradecacarbonyl (3) is formed in 65% yield. The coordination sphere of the rhodium(III) atom in compound 2 and of the rhodium(I) atom in 3 is completed by a coordination of the quinolyl moiety. This was revealed by NMR spectroscopy as well as by X-ray analyses.
Available online 3 August 2004
Gesehen am 18.11.2022